La experiencia laboral costarricense, para contrarrestar los efectos del coronavirus (covid-19) - Briones Briones, Eric (2026)
On the occurrence of the worldwide CORONAVIRUS pandemic (COVID-19), there have been changes in every labor law in order maintain labor relations under the principle of continuity and the right to work, as the prime driving force of humanity. This is why this essay aims to address the changes that Costa Rican labor law has undergone, which does not prevent a general review of the changes in other American countries, as a consequence of a global need. Therefore, this essay presents a systematic approach to the institutes devised to face the labor crisis. The aim is to set out a historical framework for theoretical/practical reference, so that future generations can learn how the pandemic was resolved in the field of our discipline and to project the upcoming changes arising as a consequence of the pandemic. The sole purpose of such analysis is that if a crisis like this occurs again, these experiences and reflections can help out in the future.